2017
DOI: 10.1111/pbi.12710
|View full text |Cite
|
Sign up to set email alerts
|

High‐yield secretion of recombinant proteins from the microalga Chlamydomonas reinhardtii

Abstract: SummaryMicroalga‐based biomanufacturing of recombinant proteins is attracting growing attention due to its advantages in safety, metabolic diversity, scalability and sustainability. Secretion of recombinant proteins can accelerate the use of microalgal platforms by allowing post‐translational modifications and easy recovery of products from the culture media. However, currently, the yields of secreted recombinant proteins are low, which hampers the commercial application of this strategy. This study aimed at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 77 publications
4
84
0
Order By: Relevance
“…In addressing the low protein productivity challenge, we engineered designer HypGP modules as molecular carriers to boost secreted protein yields. This technology was previously developed in tobacco cell culture, and most recently demonstrated in microalgae culture, to dramatically increase secreted protein yields (Ramos-Martinez et al, 2017;Xu et al, 2007Xu et al, , 2010Zhang et al, 2016b). However, the broader application of this technology in differentiated plant organs, such as hairy roots or even whole plants, has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addressing the low protein productivity challenge, we engineered designer HypGP modules as molecular carriers to boost secreted protein yields. This technology was previously developed in tobacco cell culture, and most recently demonstrated in microalgae culture, to dramatically increase secreted protein yields (Ramos-Martinez et al, 2017;Xu et al, 2007Xu et al, , 2010Zhang et al, 2016b). However, the broader application of this technology in differentiated plant organs, such as hairy roots or even whole plants, has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The function of the engineered HypGPs as a molecular carrier was hypothesized to promote efficient transport of the fused proteins across the plasmalemma and for protecting the proteins from proteolytic degradation (Zhang et al, 2016b). Besides higher plant cells, engineering HypGPs comprised of a (SP) n motif (n = 10, 20) in green microalgae (Chlamydomonas reinhardtii) was recently reported to increase the secreted yields of a reporter protein by up to 12-fold (Ramos-Martinez et al, 2017). However, the precise process for Hyp-O-glycosylation of the designer HypGPs, particularly the AGPs-like modules that undergo Hyp-O-glycosylation with complex polysaccharides in plant cells, is poorly understood (Showalter and Basu, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies indicated that the glycosylated HypGP module could function as a 'molecular carrier' to boost the secretion of fused proteins, including interferon α2b, human growth hormone and green fluorescent protein, presumably by facilitating efficient transport of the proteins into extracellular space and preventing proteolytic degradation of the proteins [20,21,24]. Most recently, the HypGP engineering technology was extended to green microalgae (Chlamydomonas reinhardtii), where engineering (SP) n tags (n = 10, 20) enhanced the secreted yields of a fused protein by up to 12-fold [25].…”
Section: Introductionmentioning
confidence: 99%
“…Mixotrophic growth, although failing to fully exploit the free carbon and energy available through photosynthesis, improves growth rates and yields in cyanobacteria Matson and Atsumi, 2018) and may be required to reach maximum potential. An underdeveloped opportunity for metabolic engineering applications is the use of consortia, where a photosynthetic microbe provides the sugar or other carbon source for a heterotroph that acts as the production platform (Ducat et al, 2012;Fedeson and Ducat, 2017;Ramos-Martinez et al, 2017). This provides the benefits of both photoautotrophy and engineerability.…”
Section: Discussionmentioning
confidence: 99%